Musculoskeletal risk stratification tool to inform a discussion about face-to-face assessment during the COVID-19 pandemic. Issue 1 (26th September 2020) - Ravindra, Andrea; Cuff, Andrew; Bernstein, Ian A; Al-Dawoud, Marwan
Abstract : The COVID-19 pandemic and lockdown caused clinicians in the UK to switch to delivering musculoskeletal care using telephone or video consultations. NHS England (an executive non-departmental public body of the Department of Health and Social Care, England) recommended prioritisation of more urgent conditions, including those people whose condition has deteriorated and those waiting the longest as part of a phased return to pre-COVID-19 service provision. Clinicians will need to assess an individual's risk factors for complications from COVID-19 alongside their clinical priority to inform a shared decision-making discussion about appropriate face-to-face care delivery. This paper outlines a risk stratification tool that informs that discussion and aims to reduce the subjectivity in the risk assessment between clinicians.